A Monolithic Graphene‐Functionalized Microlaser for Multispecies Gas Detection. Issue 51 (14th November 2022) - Guo, Yanhong; Li, Zhaoyu; An, Ning; Guo, Yongzheng; Wang, Yuchen; Yuan, Yusen; Zhang, Hao; Tan, Teng; Wu, Caihao; Peng, Bo; Soavi, Giancarlo; Rao, Yunjiang; et al.
Abstract: Optical‐microcavity‐enhanced light–matter interaction offers a powerful tool to develop fast and precise sensing techniques, spurring applications in the detection of biochemical targets ranging from cells, nanoparticles, and large molecules. However, the intrinsic inertness of such pristine microresonators limits their spread in new fields such as gas detection. Here, a functionalized microlaser sensor is realized by depositing graphene in an erbium‐doped over‐modal microsphere. By using a 980 nm pump, multiple laser lines excited in different mode families of the microresonator are co‐generated in a single device. The interference between these splitting mode lasers produce beat notes in the electrical domain (0.2–1.1 MHz) with sub‐kHz accuracy, thanks to the graphene‐induced intracavity backward scattering. This allows for lab‐free multispecies gas identification from a mixture, and ultrasensitive gas detection down to individual molecule. Abstract : The combination of 2D materials and optical microcavities offers a powerful tool to develop fast and precise sensing techniques. In this work, graphene‐enabled splitting modes in a monolithic microsphere laser are used to obtain multispecies gas detection (CO2, NH3, NO2,  and H2 O) with extremely high sensitivity down to individual molecules.